PORTALBIN sebagai inovasi platform pengelolaan sampah rumah tangga berbasis Ecopreneur digital bagi masyarakat Desa Wadung, Pakisaji, Malang - Anjar Nur Ramadhani; Ade Siyanti Nurul Hidayah; Yoyok Adisetio Laksono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Household waste is waste that comes from daily activities in the household which does not include feces and specific waste. Improper waste management can have a negative impact on the surrounding environment. Based on the complaints of the people of RT 09 RW 03 in Wadung Village, waste processing in the area is considered not to be carried out comprehensively and caused a negative impact, such as air pollution which also affect the level of public health. Wadung Village needs digital media to improve skills in waste management. A simple media website, which is able to provide education about waste and the use of high-value products is expected to be able to provide solutions for the local community. Through the Community Service Student Creativity Program, we have a solution called